Conditions of self-assessment in the faculty of education university of national Hermilio Valdizán Huánuco 2007 - Portocarrero Merino, Ewer (2009)
The objetive of study to determine the status of the conditions for self-education in the Faculty of National University Hermilio Valdizán of Huánuco. Was a simply a descriptive study with 27 teachers and 120 students from the Faculty in studing, during the period 2007. The data were drawn from a questionnaire self-assessment of the conditions under study. Specifically School education has unsuited conditions, only an operational plan and not a committee obviousness self-assessment or selfassessment activities within the Strategic Plan of the university, also the Statute of the university does not have articles concerning the powers of self-evaluation and The General Rules of the university does not have articles concerning the powers of self-evaluation. Similarly perceptions of the authorities, teachers and students of the Faculty are similar to what has already been mentioned. The conditions for self-assessment of the Faculty of Education Sciences not implemented for the due process required that is self conditions are unfavourable, it to need conditions of quality.